2004
DOI: 10.1074/jbc.m407412200
|View full text |Cite
|
Sign up to set email alerts
|

Release Factors eRF1 and RF2

Abstract: Class I release factors 1 and 2 (RF1 and RF2) terminate protein synthesis by recognizing stop codons on the mRNA via their conserved amino acid motifs (NIKS in eRF1 and SPF in RF2) and by the conserved tripeptide (GGQ) interactions with the ribosomal peptidyltransferase center. Crystal structures of eRF1 and RF2 do not fit their ribosomal binding pocket (ϳ73 Å). Cryoelectron microscopy indicates large conformational changes in the ribosome-bound RF2. Here, we investigate the conformational dynamics of the eRF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Molecular modeling showed that eRF1 can undergo a significant conformational change in the ribosome (37,38), as suggested earlier (36). Because of this change, the NIKS and YxCxxxF motifs become proximal to the stop codon at the A site (38), which implies that, for these eRF1s, a probable mechanism for stop codon restriction is associated with an interaction in space between discriminator and recognition sites, leading to local conformational changes of the latter.…”
Section: Discussion Functional Assays For Measuring Decoding Specificmentioning
confidence: 91%
“…Molecular modeling showed that eRF1 can undergo a significant conformational change in the ribosome (37,38), as suggested earlier (36). Because of this change, the NIKS and YxCxxxF motifs become proximal to the stop codon at the A site (38), which implies that, for these eRF1s, a probable mechanism for stop codon restriction is associated with an interaction in space between discriminator and recognition sites, leading to local conformational changes of the latter.…”
Section: Discussion Functional Assays For Measuring Decoding Specificmentioning
confidence: 91%
“…Cryo-EM and recent X-ray structure analysis of Escherichia coli and Thermus thermophilus ribosomes in complex with the corresponding class I RFs resolved this conflict by identification of elongated RFs bound to terminating ribosomes (22,26,27). This model of conformational adaptation of RFs upon ribosomal binding is supported by a molecular dynamic study (28). …”
Section: Introductionmentioning
confidence: 78%
“…Opening of the compact core exposes conserved hydrophobic residues at the interface between domains III and II·IV and increases the water accessible surface by 15% (27). It was suggested that the conformational transition of RF2 between free and ribosome-bound states are controlled by protonation of conserved histidines (28). Indeed, it can be expected that the overall negative charge of the ribosome will enhance the histidine protonation of RF2.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the NIKS and GGQ domains are separated by 100 Å in the crystal structure, whereas the distance between the codon in the A-site and the peptidyl center is around 73 Å. A conformational change has been modeled to create a closed form, which fits the range needed for functional binding of eRF1 within the ribosome (33). The closed conformation of eRF1 involves motion of domain 2 relative to other domains.…”
Section: Discussionmentioning
confidence: 99%